Rethinking the provision of public services and equivalent living conditions. Perspectives and fields of action. - Bojarra-Becker, Elke; Beckmann, Klaus J.; Danielzyk, Rainer; Dehne, Peter; Eltges, Markus; Köckler, Heike; Ritzinger, Anne; Schäde, Gerd; Stielike, Jan Matthias; Trautz, Alexandra (My University, 2021)
Given the fundamental change in the framework conditions and the public sector’s limited resources for action, it is appropriate to examine the issue of safeguarding equivalent living conditions and to take a position on this from the perspective of spatial science and spatial planning. The ARL - Academy for Territorial Development in the Leibniz Association sees itself as a forum in which to drive forward dialogue with all stakeholders from science, planning practice, policymakers and society. In this ARL position paper ‘Rethinking the provision of publicservices and equivalent living conditions perspectives and fields of action’ ̈the authors present starting points for discussion and call for a constructive and open review of new approaches to solutions and thinking, without prior assumptions.
Keywords: Raumordnung; Regionalplanung; Raumplanung; Planungsaufgabe; Gleichwertigkeit; Lebensbedingungen; Daseinsvorsorge; Regionale Disparität; Raumordnungspolitik; Gleichwertige Lebensverhältnisse